ANALISIS RESEPSI KHALAYAK TERKAIT TRANSGENDER DALAM FILM PRETTY BOYS - Rizky Widya Fadhila (2022)
Film is a medium of representation of reality that has the ability to create meaning. There is a film called Pretty Boys (2019) which forms the meaning of transgender in it. Transgender as an active audience also has a role in interpreting messages related to their identity which is formed in the film based on their experience or knowledge. This study aims to determine the meaning of transgender as an active audience related to the formation of the meaning of transgender self-identity made by the film 'Pretty Boys'. This study uses a qualitative approach. The paradigm used is constructivism with the Stuart Hall reception analysis research method. This method produces dominant, negotiating, and opposition categories. The sampling technique was done by purposive sampling.The results of the study found that one informant was in the dominant category, three informants were in the negotiation category, and one informant was in the opposition category. There are several contextual factors that support their meaning of transgender, including factors of experience, values, environment, education, gender, culture, norms, sexual orientation, and religion.